Associations between sense of purpose and romantic relationship quality in adulthood. (May 2020) - Pfund, Gabrielle N.; Brazeau, Hannah; Allemand, Mathias; Hill, Patrick L.
The current studies investigated the extent that sense of purpose is associated with desirable relationship variables, such as relationship satisfaction, relationship commitment, perceived quality of alternatives, and investment size. Data were collected from two online surveys of 1, 001 and 1, 594 participants in relationships (Study 1: M = 46.68, SD = 15.77, range = 18–86; Study 2: M = 52.52, SD = 16.05, range = 18–91). Study 1 found that sense of purpose was positively associated with relationship satisfaction, commitment, and negatively associated with the perception that one's partner was preferable to alternatives. When controlling for affective well-being and the Big Five personality traits, sense of purpose was still associated with relationship commitment and the perception that one's partner was preferable to alternatives. Study 2 found that sense of purpose was positively associated with relationship satisfaction, commitment, and investment size (which was exclusively assessed in Study 2), but it was not significantly associated with perceived quality of alternatives. These associations held when controlling for affective well-being and the Big Five personality traits. Across both studies, age did not consistently moderate the associations between sense of purpose and relationship satisfaction, commitment, and perceived quality of alternatives. These studies suggest that sense of purpose and aspects of relationship quality are positively associated across adulthood. Findings are discussed with respect to how purpose may be considered in future close relationship research.